Takhrij Hadith of the Law of Buying and Selling Transactions - Arrobany, Alfy Awal; Darmalaksana, Wahyudin (Journal of Takhrij Al-Hadith, 2022)
This study aims to discuss the hadith about buying and selling. This research uses a qualitative approach by applying descriptive analytical method. The formal object of this research is the takhrij hadith within the scope of hadith science, while the material object of this research is the hadith about buying and selling. The results and discussion show the Hadith of Tirmidhi History No. 1052 concerning the sale and purchase of valid quality so that it is maqbul as the basis for the implementation of Islam in the implementation of buying and selling transactions. This study concludes that the hadith narrated by Tirmidhi No. 1052 has the qualifications maqbul ma'mul bih for the basis of the implementation of buying and selling transactions in Islam, where the seller must act honestly based on goodness and the perpetrators of buying and selling are prohibited from cheating. Hadith narrated by Tirmidhi No. 1052 concerning relevant buying and selling is used as the basis of Islamic law.